Extensão universitária em oftalmologia veterinária - Frontana, Marina Salvador Gonzalez [UNESP]; Gandolfi, Micaella Gordon [UNESP]; Midori, Luciana Murata [UNESP]; Guberman, Úrsula Chaves [UNESP]; Nabessima, Camilla [UNESP]; Merlini, Natalie Bertelis [UNESP]; Hirota, Inajara Nakamura [UNESP]; Chaguri, Maria Clara Ferreira [UNESP]; Ranzani, José Joaquim Titton [UNESP]; Brandão, Cláudia Valéria Seullner [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this extension project is to attend owners population of dog presenting eye diseases and aid veterinarians of the Ophthalmology Service of the School of Veterinary FMVZ - UNESP Botucatu. Based on the data collected, easy to understand brochures were prepared for the population, with information about Uveitis in Ehrlichiosis, Cataracts, Entropion in dogs, Ulcer Cornea, Eyelid tumors and Keratoconjunctivitis Seca in dogs. It was observed an increase of the number of ophthalmological services requested by owners who identified ocular signs, many of which were described in the brochure.

Objetivou-se o atendimento de proprietários dos animais apresentando afecções oftalmológicas e auxílio à Médicos Veterinários no Serviço de Oftalmologia da FMVZ-Botucatu. Com base na casuística de atendimento foram confeccionados folders de fácil compreensão e de caráter informativo para toda a população sobre Uveíte na Erliquiose, Catarata, Entrópio em Cães, Úlcera de Córnea, Tumores Palpebrais e Ceratoconjuntivite Seca em Cães. Notou-se maior procura pelo serviço por proprietários que identificaram sinais clínicos oculares, sendo alguns descritos nos folders.
Keywords: Ocular diseases; Pet; Life quality; Afecções oftalmológicas; Animais de companhia; Qualidade de vida